Development of non-enzymatic cholesterol bio-sensor based on TiO2 nanotubes decorated with Cu2O nanoparticles - Khaliq, Nilem; Rasheed, Muhammad Asim; Cha, Gi; Khan, Maaz; Karim, Shafqat; Schmuki, Patrik; Ali, Ghafar (Sensors and Actuators B-Chemical, 2020)
A novel amperometric non-enzymatic cholesterol biosensor based on Cu2O-TiO2 hybrid nanostructure has been studied. TiO2 nanotubes (TNTs) were synthesized via anodization of titanium (Ti) foils and subsequently decorated with Cu2O nanoparticles (NPs) using chemical bath deposition (CBD) method. Incorporation of Cu2O NPs on TNTs have resulted in the high electroactive surface area which enhanced the electron transfer rate at the surface of the electrode. Cyclic voltammetry (CV) and amperometric response of the fabricated electrode exhibited high catalytic activity towards the cholesterol oxidation. The hybrid electrode demonstrated 5-fold increase in the sensitivity (∼6034.04 μAmM−1 cm−2) compared to pristine with low detection limit (∼0.05 μM) and fast response time (3 s). Moreover, the real time analysis of the cholesterol in human blood serum offered favorable accuracy with reference to the commercially available cholesterol biosensors. This study shows potential application of Cu2O NPs decorated TNTs for the development of highly stable, reproducible, and selective biosensor.
CRIS-Team Scopus Importer:2019-10-15
Keywords: Amperometry; Biosensor; Cholesterol; Copper oxide; Titanium oxide nanotubes